Poultry litter of wood shavings and/or sugarcane bagasse: animal performance and bed quality - Teixeira, Adriely S; de Oliveira, Maria C; Menezes, June F S; Gouvea, Bruno M; Teixeira, Sonia R; Gomes, Alex R (Revista Colombiana de Ciencias Pecuarias, 2015)
Background: litter provides comfort to animals while improving productive performance and carcass quality. Objective: this study evaluated broiler performance, incidence of contact dermatitis, and quality of poultry litter of wood shavings and/or sugarcane bagasse (SB) after five consecutive flocks. Methods: two thousand birds were raised in five consecutive flocks composed of 400 chicks each. The experiment was set in a completely randomized design with five treatments and four repetitions. The treatments consisted of substituting wood shavings with different levels of SB (0, 25, 50, 75, and 100%). Results: litter density, pH, dry matter content, total nitrogen, and phosphorus did not vary between treatments. However, substituting wood shavings with SB increased moisture retention capacity of the litter and ammonia production. Neither carcass lesions nor productive performance, with the exception of weight gain and feed conversion ratio in the fifth flock, differed between treatments. Conclusions: substituting 75% of wood shavings with SB maintained litter quality and improved poultry performance.